Comparative Analysis of the Residual Income Valuation Model and the Dividend Discounting Model in Predicting Stock Prices of LQ45 Companies - Icha Mustamin; Amiruddin; Darmawati; Endang Sriningsih (Indonesian Journal of Advanced Research, 2026)
This study aims to analyze and compare the effectiveness of the Residual Income Valuation (RIV) model and the Dividend Discount Model (DDM) in predicting stock prices for companies listed on the LQ45 index of the Indonesia Stock Exchange. Changes in dividend policies and market uncertainty in Indonesia necessitate the use of accurate valuation models for investors and regulators. The research method used is a quantitative comparative study employing a multiple linear regression approach. The sample was determined using purposive sampling, which included LQ45 index companies with complete financial statement data available during the observation period. The effectiveness of the models was measured using statistical instruments and prediction accuracy measures such as Mean Absolute Percentage Error (MAPE) and Root Mean Square Error (RMSE). The results of the study indicate that, taken together, net income, book value of equity, and dividends have a significant impact on stock prices, explaining 65.8% of the variance. However, when considered individually, dividends per share were found to be the most dominant and significant variable influencing stock prices (Sig. 0.000). Conversely, net income and book value of equity did not show a significant independent effect. Thus, this study indicates that in the context of LQ45 companies, the Dividend Discount Model (DDM) proves to be more relevant and has stronger predictive power compared to the RIV model. These findings suggest that investors in the Indonesian capital market still heavily rely on dividends as the primary signal of a company’s stability and quality.